Development of Power Point Learning Media Based on Canva Application in History Subjects in Senior High School - Patricia, Eka Rita Permata; Susanti, L.R. Retno (research, training and philanthropy institution Natural Aceh, 2024)
The study's formulation of the problem is how to develop valid Canva application-based PowerPoint learning media and have a practical impact on the history learning outcomes of class X Senior High School students. This project aims to produce useful Canva application-based PowerPoint learning media and determine its effectiveness on the history learning outcomes of high school X-grade students. The ADDIE model is a guide for creating learning media in this study. Media professionals and material experts tested the learning media the researcher made. Media validity is 4.73, which is in the highly valid category, while material validity is 3.86, which is in the valid category. The findings demonstrated a considerable difference between the student's pre- and post-test average scores. Compared to the pre-test, the post-test has a higher average value. After utilizing Canva application-based PowerPoint learning materials, learning outcomes increased by 44.84%, resulting in a Ngain of 0.75 with a high criterion (very effective). Thus, class X high school students' historical learning results can be significantly enhanced using Canva application-based PowerPoint learning materials in their learning sessions.